EUPHEMISTIC EXPRESSIONS IN BAJAWA LANGUAGE FOUND IN THE SOCIAL CONTEXT - Waso, Tarsisius; Kanisius, Rambut; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2022)
This study aimed at finding the types and functions of euphemistic expressions in Bajawa language that are found in the social context. In this study, the writer determines the types of euphemisms in Bajawa language that are found in the social context based on theory proposed by Nichol (2011), namely: abstraction, indirect, litotes, mispronunciation, modification, personification, and slang. And the writer describes the functions of euphemisms in Bajawa language that are found in the social context based on the theory proposed by Burridge (2012, 67-71), namely: protective, underhand, uplifting, provocative, cohesive, and ludic. The subjects in this study were members of the Rakalaba village community as Bajawa language speaker and the object of this study was the expressions of euphemistic in the form of sentences, phrases, and words used in everyday life. The data in this study using interviews, observation, and document study methods. Qualitative descriptive methods are used to provide a comprehensive description and find the types and functions of euphemistic expression. Then, the data is analyzed by grouping data on euphemisms in Bajawa language which are found into seven types of euphemisms and describing the functions of euphemisms into six functions of euphemisms. The results of this study indicate that among the seven types of euphemisms proposed by Nichol (2011), only three types of euphemisms in Bajawa language were found in the social context, namely: (1) abstraction, (2) indirection, and (3) slang. And the writer also found that among the six euphemistic functions proposed by Burridge (2012, 67-71), only five euphemistic functions were used in Bajawa language, namely: (1) protective, (2) underhand, (3) uplifting, (4) provocative, and (5) cohesive.